Work stress, work-family conflict, and psychological distress among resort employees: a JD-R model and spillover theory perspectives - Abdou, Ahmed Hassan; El-Amin, Maha Abdul-Moniem Mohammed; Mohammed, Elham Farouq Ali; Alboray, Hanem Mostafa Mohamed; Refai, Aza Mohamed Sediek; Almakhayitah, Muhanna Yousef; Albohnayh, Abdullah Saleh Mohammed; Alismail, Abdulaziz Mohammed; Almulla, Mazen Omar; Alsaqer, Jawharah Saleh; Mahmoud, Maha Hassanein; Elshazly, Adel Ibrahim Abdullah; et al. (Frontiers in Psychology, 2024)
The hospitality industry is well-known for its challenging and high-pressure work settings. In this context, employees commonly face a multitude of stressors originating from their roles and job responsibilities, which can significantly impact their psychological well-being. Hence, based on the job demands-resources (JD-R) model and the spillover theory, this study aims to empirically explore the direct and indirect effect of work stress (assessed by role overload, ambiguity, and conflict) on psychological distress among frontline employees in 3-and 4-star Egyptian resorts while considering the mediating influence of work-family conflict (WFC). Four hypotheses were put to the test through the application of the PLS-SEM 4.0 version (4.0.9.9). Based on the findings from 563 frontline employees who participated in this research, the study supports the four hypotheses affirming that work-related stressors significantly contributed to employees' psychological distress. Further, the findings highlighted that these stressors significantly spill over into employees' family lives, generating conflicts between work and family roles. In addition, the results emphasized the significance of WFC as a contributing factor to employees' psychological distress. Finally, the study concluded that WFC partially mediates the link between work stress and employees' psychological distress. Based on these findings, some theoretical and practical implications for hospitality scholars, resort management, and policymakers were suggested to enhance the employees' well-being and mitigate psychological distress in this vital sector.